Weisheit und Prädestination : weisheitliche Urordnung und Prädestination in den Textfunden von Qumran - Lange, Armin, 1961- (Studies on the Texts of the Desert of Judah, 1995)
In the attempt to overcome the crisis of knowledge in wisdom thought, even the non-Essene texts from Qumran developed the wisdom notion of a pre-existent order of being and history which was to be realised in the Eschaton. This notion was taken up in non-wisdom texts and elaborated into a dualistic ordering of the world and of history, structured in epochs. In this form the notion was used by the Essene community to deal theologically with their negative experience of reality (schism, persecution by Hasmonoaeans, delay of the Eschaton). The results of this investigation are thus able to confirm critical points of the thesis of G. von Rad that apocalyptic developed out of wisdom.